In situ Detection of Microbial Life in the Deep Biosphere in Igneous Ocean Crust - Salas, Everett C.; Bhartia, Rohit; Anderson, Louise; Hug, William F.; Reid, Ray D.; Iturrino, Gerardo; Edwards, Katrina J. (Frontiers in Microbiology, 2015)
The deep biosphere is a major frontier to science. Recent studies have shown the presence and activity of cells in deep marine sediments and in the continental deep biosphere. Volcanic lavas in the deep ocean subsurface, through which substantial fluid flow occurs, present another potentially massive deep biosphere. We present results from the deployment of a novel in-situ logging tool designed to detect microbial life harbored in a deep, native, borehole environment within igneous oceanic crust, using deep ultraviolet native fluorescence spectroscopy. Results demonstrate the predominance of microbial-like signatures within the borehole environment, with densities in the range of 105 cells/mL. Based on transport and flux models, we estimate that such a concentration of microbial cells could not be supported by transport through the crust, suggesting in situ growth of these communities.